Snake venom cardiotoxin induces G-actin polymerization - Chen, Yee-Hsiung; Chu, Sin-Tak (Biochimica et biophysica acta, 1988)
Snake venom cardiotoxin showed the ability to induce polymerization of G-actin from rabbit skeletal muscle in a low ionic strength buffer composed of 0.2 mM CaCl 2/0.2 mM ATP/0.5 mM mercaptoethanol/2.0 mM Tris-HCl, pH 8.0. The activity was enhanced greatly when 0.4 mM MgCl 2 was present in the buffer and could be inhibited if G-actin was preincubated with deoxyribonuclease I. Furthermore, the DNAase could also partially depolymerize actin polymer previously formed by the interaction of G-actin with the toxin.